Systematic Literature Review: Determinants and Financial Consequences of Corporate Effective Tax Rate (ETR) in Emerging and Developed Markets - Emi Masyitah; Leni Deli (International Journal of Economic, Technology and Social Sciences (Injects), 2026)
The Effective Tax Rate (ETR) is widely utilized in the empirical accounting and corporate finance literature as a robust proxy for corporate tax planning, compliance, and aggressiveness. This study provides a comprehensive Systematic Literature Review (SLR) focusing on the key determinants and financial consequences of ETR over the past two decades (2005-2025). Employing a rigorous SLR framework following the PRISMA protocol, we synthesized 52 empirical articles retrieved exclusively from leading international databases indexed by Scopus (Q1–Q4). Moving beyond localized research biases, this review explicitly balances the jurisdictional dynamics between developed and emerging economies while exploring the emerging impact of the digital economy on corporate tax behavior. The synthesis reveals that internal corporate attributes (such as firm size, leverage, and capital intensity) and external macro-environmental pressures represent the critical determinants shaping corporate ETR strategies. Furthermore, our findings indicate that ETR optimization exhibits multi-directional impacts on financial performance (ROA, ROE) and corporate value, which are heavily moderated by corporate governance frameworks, information asymmetry, and ESG mandates. Ultimately, this review exposes critical research gaps regarding AI driven predictive tax planning and establishes a strategic framework for future cross border empirical tax research.